2003
DOI: 10.1038/nature01774
|View full text |Cite
|
Sign up to set email alerts
|

The break-up of heavy electrons at a quantum critical point

Abstract: The point at absolute zero where matter becomes unstable to new forms of order is called a quantum critical point (QCP). The quantum fluctuations between order and disorder 1-5 that develop at this point induce profound transformations in the finite temperature electronic properties of the material. Magnetic fields are ideal for tuning a material as close as possible to a QCP, where the most intense effects of criticality can be studied. A previous study 6 on theheavy-electron material Y bRh 2 Si 2 found that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

64
821
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 701 publications
(892 citation statements)
references
References 16 publications
64
821
7
Order By: Relevance
“…between non-Fermi liquid and LFL behavior is accompanied by unique T /b scaling in thermodynamic and transport properties observed over nearly four decades in temperature over magnetic field [1]. It indicates that the characteristic energy of the heavy quasiparticles is governed only by the ratio of the thermal energy to the magnetic field increment b and vanishes upon approaching the QCP.…”
mentioning
confidence: 90%
“…between non-Fermi liquid and LFL behavior is accompanied by unique T /b scaling in thermodynamic and transport properties observed over nearly four decades in temperature over magnetic field [1]. It indicates that the characteristic energy of the heavy quasiparticles is governed only by the ratio of the thermal energy to the magnetic field increment b and vanishes upon approaching the QCP.…”
mentioning
confidence: 90%
“…Indeed, the measurements on these metals have shown that the Grüneisen ratio diverges [2,20,21]. In that case, the electronic systems of these metals are to undergo FCQPT so that the temperature independent part S 0 of the entropy becomes finite [18].…”
Section: Asymmetric Conductance In Hf Metals and Htscmentioning
confidence: 99%
“…It has emerged at the front and center of the physics of strongly correlated electron systems known to host competing quantum orders, and is witnessed by a proliferation of reports on heavy Fermions (2)(3)(4)(5), itinerant (quantum) magnets (6), and hightransition-temperature (high-T c ) superconductors (7), with quantum matter tuned (at times arguably) through a transition by pressure, magnetic field, or doping-arguably because one has to rely on long shadows cast by quantum criticality far above zero temperature (8), for, obviously, T ϭ 0 K cannot ever be attained.…”
mentioning
confidence: 99%